(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper adopts a conceptual and desk-review approach in examining the influence of digital product innovation strategies on organizational performance of public universities in Kenya. The increasing pressure on universities to remain competitive in an increasingly digital environment has necessitated the adoption of innovative approaches aimed at improving organizational performance. This study examined the influence of digital product innovation strategies on organizational performance of public universities in Kenya. Digital product innovation strategies were operationalized through research and development initiatives, innovation centers and hubs, and intellectual property management. Organizational performance was measured using student enrollment, employee turnover, and access to information. The study focused on Resource-Based View Theory proposed by Barney (1991) and Dynamic Capabilities Theory advanced by Teece et al. (1997). These theories explain how organizations use internal resources, innovation skills, and flexible abilities to gain a lasting edge over competitors. Recent research has highlighted the importance of these theories in understanding organizational performance and digital changes in fast-moving environments. (Civelek et al., 2023; Gohr et al., 2023); Heaton et al., 2023). This study utilized Desktop review methodology through narrative literature synthesis. Findings indicate that digital product innovation strategies positively influence organizational competitiveness, accessibility of university services, and institutional attractiveness to prospective students.